(untitled) (Geografares, 2011)
Esse artigo tem por objetivo enfatizar, na análise o meio rural contemporâneo, a dimensão do território, considerando a superação de uma visão de rural associado a atividades agrícolas strictu sensu, e na pior das hipóteses, à decadência sócio-econômica das áreas rurais ante a urbanização. Deste modo, os Arranjos produtivos locais aparecem como instrumentos importantes para a análise territorial do desenvolvimento rural, sobretudo por sua capacidade de associar em meios periurbanos e semi-rurais, o ´empreendedorismo` local com as atividades inovadoras com forte conteúdo em ‘capital social’. A fim de ratificar tais hipóteses, a luz do exemplo bem sucedido de dinamismo econômico proporcionado pelos distritos industriais marshallianos em regiões italianas semi-rurais, coloca-se como base empírica de análise um estudo de Arranjo produtivo brasileiro voltado a um tipo de atividade tipicamente rural: a produção de mandioca realizada no Sudeste do Mato Grosso do Sul. New dimensions of rural: Territory and local productive arrangements Abstract This article aims to emphasize, in the analysis to the contemporary rural space, the dimension of territory, considering the overcoming of a rural perspective associated with the agricultural activities in the strict sense, and at worst hypothesis, at the socio-economic decline of rural areas in the face of urbanization. Thus, the local productive arrangements appear as important tools for the analysis to rural development, especially for its ability to associate, at peri-urbanand semi-rural spaces, the ’entrepreneurial’ local with innovative activities of strong content in’social capital’ . In order to confirm these hypotheses, the light of the successful example ofeconomic dynamism provided by the Marshallian industrial districts in semi-rural Italian regions, there is empirical analysis based on a study of Brazilian production arrangementaimed at a rural typical type of activity: cassava production established in south-eastern MatoGrosso do Sul. DOI: 10.7147/GEO9.1350